2008
DOI: 10.2478/v10034-008-0024-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Y Isodicentrics in two Cases with Ambiguous genitalia and Features of Turner Syndrome

Abstract: Karyotype investigations using classical cytogenetics, fluorescence in situ hybridization (FISH) and polymerase chain reaction (PCR) techniques were used for the characterization of Y chromosome structural anomalies found in two patients with ambiguous genitalia and features of Turner syndrome. Both exhibited mosaic karyotypes of peripheral blood lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Two of our patients (cases 1 and 2) had a female phenotype, whereas the remaining 2 patients (cases 3 and 4) were phenotypically males. Indeed, discrepancies between phenotype and karyotype in individuals having a chromosomal mosaicism involving the Y chromosome have been reported previously [Lungeanu et al, 2008]. What do these discrepancies depend on, in addition to the cell line distribution?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of our patients (cases 1 and 2) had a female phenotype, whereas the remaining 2 patients (cases 3 and 4) were phenotypically males. Indeed, discrepancies between phenotype and karyotype in individuals having a chromosomal mosaicism involving the Y chromosome have been reported previously [Lungeanu et al, 2008]. What do these discrepancies depend on, in addition to the cell line distribution?…”
Section: Discussionmentioning
confidence: 99%
“…Y chromosome aberrations, especially of the isodicentric type are known to be very unstable during cell division, generating alternating cell lines [Marzuki et al, 2011]. Lungeanu et al [2008] suggested that in these isodicentric aberrations initially both centromeres of the Y chromosome were completely functional and that the loss of this chromosome through failure of correct mitotic segregation and anaphase produced increasing amounts of 45,X cells, thus leading to TS. Furthermore, Robinson et al [1999] hypothesized that the abnormal Y chromosome results from an error occurring during gametogenesis before the spermatid stage, or during the first division after fertilization.…”
Section: Discussionmentioning
confidence: 99%